Strengthening the “Misi Keugaharian” as A Faith and Cultural Responsibility towards The Environment for The Toraja Church Women's Fellowship (PWGT) of the Bua Tallulolo Kesu' South Toraja - Ruadjanna Tangirerung, Johana; Ammay Bungaran, Stephanus; Rejeki, Bedsy; Jona Yumarto, Ivanka; Tangkelayu, Rhuny (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
Environmental crises and degradation have become prominent issues in the past decade, exacerbated by misinterpretations of religious values and local wisdom. Rather than acting as stewards of the environment, humans have contributed to ecological problems. This Community Service Program collaborates with PWGT Bua Tallulolo, who have been identified as lacking the resources and capacity to address the environmental crisis effectively. The primary goal of this Community Service Program is to provide guidance and support in understanding the church's mission and its relationship with religious attitudes towards environmental stewardship through the "Misi Keugaharian" program. The service-learning approach was employed in this PKM, comprising four key stages: The program began with assessing core challenges faced by PWGT, followed by socialization and coaching on "Misi Keugaharian," enhancing participants' understanding of integrating ecological values. Continuous mentoring supported practical application, while the evaluation phase reviewed feedback and observed behavior changes, confirming the program’s impact and providing insights for future initiatives. The results of this PKM indicate that the members of PWGT Bua Tallulolo have successfully understood and applied the teachings of the "Misi Keugaharian" in both family and church settings. Moreover, participants have expressed a desire for future Community Service Program initiatives to focus on activities with a more direct and tangible impact on the broader community.